Long-Term Bed Rest Delays the Circadian Phase of Core Body Temperature - Mendt, Stefan; Brauns, Katharina; Friedl-Werner, Anika; Belavy, Daniel L.; Steinach, Mathias; Schlabs, Thomas; Werner, Andreas; Gunga, Hanns-Christian; Stahn, Alexander C. (Frontiers in Physiology, 2021)
Spaceflight is prone to sleep loss and circadian misalignment provoked by non-24 h light–dark cycles, acute operational shifts in sleep timing, high workload under pressure, and psychological factors. Head-down tilt bed rest (HDBR) is an established model to mimic some of the physiological adaptions observed in spaceflight. Data on the effects of HDBR on circadian rhythms are lacking. To address this gap, we investigated the effects of bed rest on circadian rhythms by analyzing the change in the circadian rhythm of core body temperature (CBT) in two 60-day HDBR studies sponsored by the European Space Agency (ESA) (n = 13 men, age: 31.1 ± 8.2 years (M ± SD)). CBT was recorded for 36 h using a non-invasive and validated dual-sensor heat flux technology during the 3rd and the 8th week of HDBR. Bed rest induced a significant phase delay (4.23 h vs. 4.68 h, p = 0.005, g = 0.85) irrespective of the study site (p = 0.416, g = -0.46), corresponding to an average phase delay of about 0.9 min per day of HDBR. In conclusion, long-term bed rest weakens the entrainment of the circadian system to the 24-h day. We attribute this effect to the immobilization and reduced physical activity levels associated with HDBR. Given the critical role of diurnal rhythms for various physiological functions and behavior, our findings highlight the importance of monitoring circadian rhythms in circumstances in which gravity or physical activity levels are altered.